Sequencing and Analysis of the Mediterranean Amphioxus (Branchiostoma lanceolatum) Transcriptome - Oulion, Silvan (Public Library of Science, 2012)
BACKGROUND: The basally divergent phylogenetic position of amphioxus (Cephalochordata), as well as its conserved morphology, development and genetics, make it the best proxy for the chordate ancestor. Particularly, studies using the amphioxus model help our understanding of vertebrate evolution and development. Thus, interest for the amphioxus model led to the characterization of both the transcriptome and complete genome sequence of the American species, Branchiostoma floridae. However, recent technical improvements allowing induction of spawning in the laboratory during the breeding season on a daily basis with the Mediterranean species Branchiostoma lanceolatum have encouraged European Evo-Devo researchers to adopt this species as a model even though no genomic or transcriptomic data have been available. To fill this need we used the pyrosequencing method to characterize the B. lanceolatum transcriptome and then compared our results with the published transcriptome of B. floridae. RESULTS: Starting with total RNA from nine different developmental stages of B. lanceolatum, a normalized cDNA library was constructed and sequenced on Roche GS FLX (Titanium mode). Around 1.4 million of reads were produced and assembled into 70,530 contigs (average length of 490 bp). Overall 37% of the assembled sequences were annotated by BlastX and their Gene Ontology terms were determined. These results were then compared to genomic and transcriptomic data of B. floridae to assess similarities and specificities of each species. CONCLUSION: We obtained a high-quality amphioxus (B. lanceolatum) reference transcriptome using a high throughput sequencing approach. We found that 83% of the predicted genes in the B. floridae complete genome sequence are also found in the B. lanceolatum transcriptome, while only 41% were found in the B. floridae transcriptome obtained with traditional Sanger based sequencing. Therefore, given the high degree of sequence conservation between different amphioxus species, this set of ESTs may now be used as the reference transcriptome for the Branchiostoma genus.